The bartonellas and Peruvian medicine : the work of Alberto Leonardo Barton - Alarcón, Graciela S.; Alarcón, Renato D. (Rutgers global health., 2019)
The Bartonellas and Peruvian Medicine explores the events surrounding the discovery of the etio-pathogenic agent of the Oroya Fever, also known as Peruvian Verruga or Carrión's disease (an endemic infectious disease in South America's Andean regions) by Dr. Alberto Leonardo Barton. Graciela S. Alarcón and Renato D. Alarcón recount Barton's persistent work against skepticism, obstacles, and limitations imposed by members of Peru's medical elites of the time, as well as his eventual successful scientific career and the delayed but well-deserved global recognition of his contributions. The book is the result of intense bibliographic research and of original documents aimed not just at the examination of Barton's life and work, but also the examination of today's perspectives and future work in the field of infectious and "neglected" diseases. The authors address current scientific information on the relevant bacteria Bartonella bacilliformis, besides current research and clinical status of the other Bartonellas, making it a useful and practical text for those studying infectious diseases